The Economics of Corporate Governance and Mergers 2008
DOI: 10.4337/9781848443921.00007
|View full text |Cite
|
Sign up to set email alerts
|

Legal Origin, Shareholder Protection and the Stock Market: New Challenges from Time Series Analysis

Abstract: This paper uses a new time series dataset of shareholder protection consisting of 60 annual legal indicators for the period 1970-2005 for France, Germany, the UK and the US. On the basis of these data it examines developments in shareholder protection and reassesses the claims that common-law countries have better shareholder protection than civil law countries. Furthermore it examines the relationship between legal changes and stock market development. It casts serious doubt on the claim that common-law count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 15 publications
(20 reference statements)
1
20
0
Order By: Relevance
“…Such time-series information has hitherto not been available. The first results from the analysis of the time-series data on shareholder protection for four OECD countries are reported in Fagernas, Sarkar and Singh (2008). 1 The present paper complements that article by further statistical and econometric analysis of the assembled data.…”
Section: Introductionmentioning
confidence: 62%
See 3 more Smart Citations
“…Such time-series information has hitherto not been available. The first results from the analysis of the time-series data on shareholder protection for four OECD countries are reported in Fagernas, Sarkar and Singh (2008). 1 The present paper complements that article by further statistical and econometric analysis of the assembled data.…”
Section: Introductionmentioning
confidence: 62%
“…This question was empirically examined in Fagernas, Sarkar and Singh (2008) integration analysis and contrary to the received literature it indicated that there is no long-term relationship between shareholder protection and the development of the stock market. The conclusion was fine as far as it went but it was subject to some important reservations.…”
Section: Shareholders' Protection and Stock Market Developmentmentioning
confidence: 92%
See 2 more Smart Citations
“…For example, a core tenet of the legal origin approach is that changes to shareholder protection law should be reflected in stock market development. Fagernäs et al (2007), using the shareholder protection index for the period 1970-2005, conduct a time series analysis to see if there is any relationship between the trend in legal change and stock market development over time in France, Germany, the UK and the US, using stock market turnover ratio as the dependent variable. No consistent relationship is found; and for the UK and France, the analysis suggests that there is (somewhat counter-intuitively) a negative relationship.…”
Section: The Legacy Of Legal Origin In the Law Governing The Busimentioning
confidence: 99%